Impact of Pain on Employment and Financial Outcomes Among Cancer Survivors. Issue 1 (1st January 2022) - Halpern, Michael T.; de Moor, Janet S.; Yabroff, K. Robin
Abstract : PURPOSE: Although pain is a frequently reported symptom among individuals with cancer, there is limited information on the impact of pain on employment or financial outcomes. This study used nationally representative data to examine the role of pain levels on employment and financial outcomes. METHODS: We used data from the 2016-2017 Medical Expenditure Panel Survey Experiences with Cancer Survivorship Supplement to identify 1, 213 adults diagnosed with cancer. Multivariable logistic regression analyses were used to examine association of pain levels and self-reported employment and financial outcomes. RESULTS: Approximately 43% of adults with a cancer history reported no pain, 29% mild pain, 18% moderate pain, and 10% severe pain over the past 7 days. Compared with those reporting no pain, individuals reporting any pain had significantly increased likelihood of adverse employment outcomes including early retirement, feeling less productive, and staying at a job because of concerns about losing insurance. Individuals with any pain (compared with no pain) also had significantly increased likelihood of adverse financial outcomes including borrowing money or going into debt, inability to cover medical costs, and worrying about paying medical bills. For both employment and financial outcomes, there were dose-response relationships, with worse outcomes generally associated with greater pain levels. CONCLUSION: Pain is frequently associated with adverse employment and financial outcomes among cancer survivors, and greater pain is associated with worse outcomes. Better assessment of pain severity among survivors and implementation of strategies to assist with employment and financial objectives may be important steps to enhance patient-centered care.